Ebooks, book history, and markers of place - Henningsgaard, Per (2019)
This article considers how markers of place function differently in the print book ecosystem vs. the ebook ecosystem, using books associated with Australia and Western Australia as a case study. Although book historians have mostly failed to engage with ebooks as subject matter, they have considered in some detail the way in which markers of place function in the print book ecosystem. By surveying the scholarly output of book historians working with mapping technologies, it is possible to conclude that, in the print book ecosystem, there exist a handful of markers identifying the following categories: places associated with a book's setting, its author, its publication, its purchase, and its marketing and publicity. The latter three markers look substantially different in the ebook ecosystem than in the print book ecosystem. Furthermore, in the ebook ecosystem, changes to these three markers can mediate setting and author as markers of place.